Febrile seizure in children with COVID-19 during the Omicron wave - Xu, Pu; Chen, Xuelian; Zhou, Jianguo; Zhou, Wenhao; Wang, Laishuan (Frontiers in Pediatrics, 2023)
Objective: To explore the clinical characteristics and prognosis of febrile seizure in children with COVID-19. Methods: This study is a single-center retrospective cohort study. The cases included febrile seizures in children with COVID-19 admitted to the Renji Hospital from April 7th, 2022 to June 2nd, 2022. We compared children with and without febrile seizures in their clinical characteristics such as sex, age, symptoms, seizure manifestation, COVID-19 severity, and SARS-CoV-2 nucleic acid test results. The children with febrile seizures were followed up by telephone and outpatient service about one month after the nucleic acid turned negative and discharged from the hospital. Results: A total of 871 pediatric COVID-19 cases were included in the analysis. There were 16 children (1.8%) with febrile seizures, age from six months to three years old, ten boys (62.5%) and six girls (37.5%). The manifestations of febrile seizures were all generalized tonic-clonic seizures. The median nucleic acid negative conversion time was 11 (IQR:10.75,13) days. Our first comparison involved comparing children without underlying diseases; there was no significant difference in sex, COVID-19 severity, and clinical manifestations, but there was an age difference (2 vs.1.3, P=0.047). There was no difference in SARS-CoV-2 nucleic acid negative time between the two groups (11d vs.13d, P=0.128). Two children had new clinical manifestations during the follow-up, but their EEG and MRI were normal. Conclusion: Febrile seizure may be children's primary neurological manifestation of COVID-19. It may occur in children with no history of epilepsy and is not associated with severe illness. The longterm neurological outcomes of these children should be followed up.